1988
DOI: 10.1161/01.cir.77.6.1245
|View full text |Cite
|
Sign up to set email alerts
|

Serum immunoglobulin E response to myocardial infarction.

Abstract: Mast cells have been implicated in the pathogenesis of coronary heart disease. They can be activated by immunoglobulin (Ig) E-mediated mechanisms to release powerful mediators affecting local blood flow. We have determined systematically serum IgE concentrations in 100 patients with acute myocardial infarction. There was a consistent pattern of change in serum IgE, characterized by a significant increase on the third and fifth day, peak values on the seventh day, and a gradual decline to initial levels by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 26 publications
6
33
0
Order By: Relevance
“…17 Several clinically relevant stimuli activate HHMC isolated from DCM, ICM, and control subjects. Serum IgE levels are increased in patients with several cardiovascular diseases, 13,14 and anti-IgE induces the release of preformed (histamine and tryptase) and de novo synthesized (LTC 4 ) mediators from cardiac mast cells. Moreover, SCF, a cytokine synthesized by fibroblasts 46 that induces mast cell growth in vitro 25,27 and in vivo, 28 activates HHMC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Several clinically relevant stimuli activate HHMC isolated from DCM, ICM, and control subjects. Serum IgE levels are increased in patients with several cardiovascular diseases, 13,14 and anti-IgE induces the release of preformed (histamine and tryptase) and de novo synthesized (LTC 4 ) mediators from cardiac mast cells. Moreover, SCF, a cytokine synthesized by fibroblasts 46 that induces mast cell growth in vitro 25,27 and in vivo, 28 activates HHMC.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of IgE antibodies are increased in the circulation of patients with cardiovascular diseases. 13,14 A polyclonal antibody against the Fc⑀ portion of IgE cased a concentration-related (3ϫ10 -1 to 5 g/mL) histamine release from HHMC from control subjects and DCM and ICM patients. In these experiments, the percent histamine did not vary among three groups examined; however, when the absolute level of release was correlated per gram of wet tissue, the difference was highly significant (Fig 7).…”
Section: Mediator Release From Isolated Cardiac Mast Cells Induced Bymentioning
confidence: 99%
See 1 more Smart Citation
“…20) Secreted IgE molecules bind to mast cells and stimulate them to release histamine, leukotrienes, and cytokines which further play major roles in perpetuating the inflammatory response and contraction of vascular smooth muscle cells. 20,21) We suggested that if mast cells contribute to the pathophysiological process of atherosclerotic plaques, stretching and tearing of the plaque as well as the involved vessel segment by stenting will be responsible for mast cell activation and kindling of an intense inflammatory reaction. A simple way to detect a mast cell-mediated reaction is possible by demonstrating an increased level of IgE which is the signal turning the mast cells on.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Elevated immunoglobulin E (IgE) levels in particular have been suggested to protect patients with acute myocardial infraction (AMI) from its complications 9,10) . Brief periods of myocardial ischemia before the onset of an acute myocardial infarction have been indicated to improve left ventricular function and shortterm outcomes.…”
mentioning
confidence: 99%